2018
DOI: 10.4103/jlp.jlp_57_17
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hemoglobin variants and hemoglobinopathies using cation-exchange high-performance liquid chromatography in central reference laboratory of India: A report of 65779 cases

Abstract: CONTEXT:Hemoglobinopathies constitute the world's most common genetically inherited red blood cell disorder. Screening and accurate identification of hemoglobin (Hb) variants have become increasingly important in antenatal diagnosis and prevention of Hb disorders.AIM:The aim of this study was to screen and identify Hb fractions prevalent in the Central Reference Laboratory of India.MATERIALS AND METHODS:A total of 65,779 cases were screened for hemoglobinopathies on the bio-rad variant high-performance liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 8 publications
0
34
0
2
Order By: Relevance
“…For example, hemoglobin C is highly prevalent in West Africa, 102 while hemoglobin E is the most prevalent in the Mediterranean region, Southeast Asia, and in the Indian subcontinent. 7,[34][35][36]43 Test location, the ethnicity of the subject, the hemoglobin percentage ( Fig. S18-S32 †), and clinical history can be used to help differentiate between comigrating hemoglobin types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, hemoglobin C is highly prevalent in West Africa, 102 while hemoglobin E is the most prevalent in the Mediterranean region, Southeast Asia, and in the Indian subcontinent. 7,[34][35][36]43 Test location, the ethnicity of the subject, the hemoglobin percentage ( Fig. S18-S32 †), and clinical history can be used to help differentiate between comigrating hemoglobin types.…”
Section: Discussionmentioning
confidence: 99%
“…8 Hemoglobin E is another common structural hemoglobin variant, but it is unique in that it also decreases expression of the β-globin gene. 7,34 Individuals with hemoglobin E trait (Hb AE or Hb E Trait) are asymptomatic, and homozygous hemoglobin E (Hb EE or Hb E Disease) causes a mild microcytic anemia. However, hemoglobin E in combination with β thal (Hb Eβ thal+/0 ) causes thalassemia of varying severity.…”
Section: Introductionmentioning
confidence: 99%
“…[4] In a multicentre study conducted in Mumbai on 65,779 patients, HbE disease (homozygous HB E/Hb E-beta-thalassemia) accounted for 0.34% of cases. [2] In a study conducted in eastern India including 119,336 cases, the prevalence of HbE/β thal was 1.16 %. [5] Conversely, a study from western India showed a prevalence of 0.2%.…”
Section: Discussionmentioning
confidence: 99%
“…It tends to elute in A2 window within the retention time ranging from 3.3 to 3.9 min. [2] Genetic factors influencing the severity and clinical diversity of this disorder include type of beta-thalassaemia mutation, co-inheritance of alpha-thalassaemia, HbA levels, polymorphisms associated with increased production of fetal haemoglobin and co-inheritance with other hemoglobinopathies. [3] Other factors include increased serum erythropoietin levels and its response to age and HbE levels, malaria infestation, previous splenectomy and other environmental influences.…”
Section: Introductionmentioning
confidence: 99%
“…from 2011-2013 in four provinces of Pakistan, the most frequent mutation detected in a total of 63 samples of β-thalassemia was IVS-I-5(G>C) (33.9%) (30). In India, more than 90% of mutations in beta thalassemia involve IVS1-5 (G >C) (31,32). Similar to our findings, studies by Silva (33) and Araujo (34) also identified this mutation in the population of Recife, Pernambuco.…”
mentioning
confidence: 99%